Impression management; a strong predictor of Organizational Citizenship Behavior: An evidence based on academicians' job insecurity, honesty-humility, reciprocity and power distance - GholamReza Zandi; Saeed Ahmad; Muhammad Sadiq Shahid; Imran Ahmed Shahzad (Cogent Business & Management, 2023)
This paper explores the relationship between impression management and organizational citizenship behavior (OCB) and how reciprocity, honesty-humility, and job insecurity determines this relationship. Data have been collected based on a sample of 710 contractual faculty members of public and private sector universities from Southern Punjab, Pakistan, upon which comparative analysis was conducted to access the behavioral intentions of respondents. Impression management acts as a mediator on the relationships between OCB and its predictors, whereas Power Distance (PD) played the role as a moderator on the relationship between impression management & OCB. As it was predicted, relationships between reciprocity, honesty-humility, job insecurity and OCB were found significantly positive through mediation. Additionally, job insecurity found having negative impact with both mediator & OCB. Further, results showed no difference between the mean of two groups (public and private respondents). Implications of the study for the policy makers and future research directions were suggested.
Keywords: 650; Honesty-humility; Impression Management; Job Insecurity; OCB; Power Distance; Reciprocity